The Impact Of Opioid Addiction On Maternal And Neonatal Health: A Comprehensive Approach To Care In Community And Intensive Care Settings, And The Pharmacological Interventions (The Review of Diabetic Studies, 2025)
Opioid addiction constitutes a significant public health concern in the U.S., particularly impacting pregnant women and driving increased consumption among women of reproductive age. This study outlines evidence-based frameworks to support nursing practices, identifies critical knowledge gaps, and emphasizes the necessity of a multidisciplinary approach to maternal and neonatal health.MethodThis study employs a quantitative, non-experimental, correlational design to examine the impact of opioid addiction on maternal and neonatal health outcomes, including an analysis of pharmacological  interventions. The research focuses on a convenience sample of 150 pregnant women with opioid use disorder (OUD) and their newborns, drawn from community and neonatal intensive care environments. Data collection, conducted over a 12-month period, involved retrospective medical record reviews and structured interviews covering demographic and clinical factors.ResultsProlonged maternal opioid consumption was significantly associated with reduced gestational age and lower birth weights, elevated Finnegan Neonatal Abstinence Scoring System (FNASS) scores, extended hospitalizations, and higher neonatal medication dosages; notably, it did not correlate with Apgar scores. Among the substances studied, fentanyl exposure led to the most adverse neonatal outcomes. Conversely, prescription opioids and illicit methadone were correlated with higher birth weights and less severe cases of Neonatal Abstinence Syndrome (NAS). While NICU admission was associated with improved Apgar ratings, it also correlated with more severe NAS and prolonged hospital stays, underscoring the need for rigorous surveillance. Furthermore, the specific type of opioid showed a substantial correlation with socioeconomic status, administration route, prenatal care quality, delivery mode, medication-assisted treatment (MAT) regimens, and depression severity, indicating distinct risk profiles for each substance category.ConclusionThe study underscores the urgent necessity for integrated prenatal interventions and comprehensive mental health support for this population; furthermore, it advocates for continued research to address existing knowledge gaps and refine clinical treatment methodologies.